The Dialectics and Dialogics of Space and Time: A Discussion of Tillich's Concept of Technology - Klaassen, Philip (My University, 1996)
Before I thank others I would like to give special thanks to my parents for their gift of the foundation of learning and inclination by which academic studies became a possibility for me. I have only begun to realize how much I am indebted to them, and the extent to which time spent with them in conversation or exploring untrodden regions of British Columbia and Yukon continues to inspire. Next I would like to thank Frank and Sharon, my brother and sister-in-law, for making their dinner table available this autumn for daily gatherings of the extended family. This has been a season of good food and my parent's excellent home-made wine. I also thank Jessica and Isaac, my niece and nephew and Emma and Brigete, the children of my roomates, for visiting me while I was writing some of the more difficult sections of this thesis and bringing me gifts of power (or so these gifts were explained to me). And I reserve my final thanks for Professor John Robertson, my supervisor, for his help and encouragement, and for introducing me to Tillich.
Keywords: Religion; Religion